Can Attention and Working Memory Impairments of Intimate Partner Perpetrators Explain Their Risky Decision Making? - Romero-Martínez, Á. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) perpetrators commonly exhibit deficits in a wide range of cognitive domains, such as attention, memory, and executive functions. Executive dysfunctions tend to be related to a preference for disadvantageous decisions, which could be explained by a pattern of focusing on positive outcomes (gains) while disregarding negative ones. Nonetheless, it is less clear whether risk-taking and decision-making problems should be attributed to motivational and/or emotional causes or to cognitive deficits in attention and/or working memory. The main goal of the present study was to examine whether IPV perpetrators can be distinguished from non-violent controls based on their performance on attention, working memory, and decision-making tests from a computerized battery of tests. In addition, this study investigated the potential relationship between attention and working memory impairments in the decision-making abilities of IPV perpetrators. Our data indicated that IPV perpetrators perform worse than controls on measures of attention and sustained attention, processing speed, working memory, spatial span, and decision making. Moreover, IPV perpetrators’ preference for disadvantageous and risky decisions could be partially explained by attention and working memory impairments. Our study has enabled us to explore the cognitive deficits underlying IPV perpetration as key factors in reducing IPV risky decisions. Moreover, it reinforces the need to develop specific neuropsychological training in the attention-switching ability in general and working memory, which could lead to improvements in decision-making processes or other executive functions.